Vulval carcinomas: an update. Issue 12 (December 2021) - Boyle, William; Ganesan, Raji
Abstract: Vulvar squamous neoplasms – intraepithelial and invasive – are now classified by their aetiological relationship with human papillomavirus. This distinction is imperfect on morphological assessment alone. This article discusses the new classification and the use of p16 and p53 in the distinction. Other recent developments, including FIGO 2021 staging of vulvar cancers, is discussed here.